A sequence-based 74plex microhaplotype assay for analysis of forensic DNA mixtures. (November 2020) - Oldoni, Fabio; Bader, Drew; Fantinato, Chiara; Wootton, Sharon C.; Lagacé, Robert; Kidd, Kenneth K.; Podini, Daniele
Highlights: 74 autosomal microhaps were compiled in a single panel and tested on the Ion Torrent S5™ system. The panel of 74 microhap loci is high sensitive to low-level DNA. The microhap assay is a powerful tool for mixture detection and deconvolution. The 74 microhaps can complement and enhances size- and sequence-based STR analysis. Abstract: Microhaplotypes are emerging biomarkers for forensic applications. In this study, a sequence-based multiplex assay of 74 microhaplotypes (230 SNPs) was developed on the Ion Torrent S5™ (Thermo Fisher Scientific) system and the potential for its application to mixture deconvolution was explored. The 74 loci are distributed across the autosomal human genome and have Ae ( i.e., effective number of alleles) values ranging from 1.307 to 6.010 (median = 2.706) and In ( i.e., informativeness) values ranging from 0.096 to 0.660 (median = 0.251); the amplicon sizes range between 157 and 325 bp. The typing performance of the panel was evaluated on a series of in-silico two to five-person DNA mixtures and results were compared to fragment and sequence-based STRs. The 74plex-locus assay was found sensitive down to 0.05 ng of input DNA and effective for the analysis of mixtures at different contributor ratios and input DNA amounts. As expected, none or very partial minor CE-STR profile(s) were reported for highly imbalanced two-person and high-order DNA mixtures while sequencing of STRs enabled the detection of more individual minor alleles. For microhaplotypes, a full minor profile was detected down to a 20:1 ratio at 10 ng and minimal allele dropout at 1 ng of input DNA. A higher rate of allele dropout from the minor donor(s) was reported at 1 ng than 10 ng for three-person mixtures while for four- and five-person mixtures, the same number of dropouts was observed for almost all minor donors. Overall this microhaplotype panel is a powerful tool that can complement and enhance size- and sequence-based STR analysis of forensic DNA mixtures.